Cover Picture: Open‐Pore Two‐Dimensional MFI Zeolite Nanosheets for the Fabrication of Hydrocarbon‐Isomer‐Selective Membranes on Porous Polymer Supports (Angew. Chem. Int. Ed. 25/2016). Issue 25 (9th June 2016) - Zhang, Han; Xiao, Qiang; Guo, Xianghai; Li, Najun; Kumar, Prashant; Rangnekar, Neel; Jeon, Mi Young; Al‐Thabaiti, Shaeel; Narasimharao, Katabathini; Basahel, Sulaiman Nasir; Topuz, Berna; Onorato, Frank J.; et al.
Abstract : Piranha fish have sharp teeth and are known for their ferocious appetite. Piranha solution, a mixture of sulfuric acid and hydrogen peroxide, is one of the strongest oxidizing agents used for the removal of organic residues, and is employed by Q. Xiao, M. Tsapatsis, and co‐workers in their Communication onpage 7184 ff. for the detemplation and exfoliation of MFI nanosheets, which enables the fabrication of hydrocarbon‐isomer‐selective membranes on polymer supports.